2019
DOI: 10.1002/path.5362
|View full text |Cite
|
Sign up to set email alerts
|

p38‐regulated FOXC1 stability is required for colorectal cancer metastasis

Abstract: Aberrant expression of forkhead box C1 (FOXC1) promotes tumor metastasis in multiple human malignant tumors. However, the upstream modulating mode and downstream molecular mechanism of FOXC1 in metastasis of colorectal cancer (CRC) remain unclear. Herein we describe a systematic analysis of FOXC1 expression and prognosis in CRC performed on our clinical data and public databases, which indicated that FOXC1 upregulation in CRC samples was significantly associated with poor prognosis. FOXC1 knockdown inhibited m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 50 publications
(49 reference statements)
0
19
0
Order By: Relevance
“…In these studies, overexpression led to the development of an increased number of metastatic lesions in preclinical animal models. Conversely, siRNA-mediated knockdown of FOXC1 practically abolished metastatic propensity (49,54,85) in most of these models, confirming the critical dependence of these cancers on FOXC1 to drive the metastatic program.…”
Section: Foxc1: a Functional Driver Of Cancer Progression And Metastasismentioning
confidence: 55%
See 2 more Smart Citations
“…In these studies, overexpression led to the development of an increased number of metastatic lesions in preclinical animal models. Conversely, siRNA-mediated knockdown of FOXC1 practically abolished metastatic propensity (49,54,85) in most of these models, confirming the critical dependence of these cancers on FOXC1 to drive the metastatic program.…”
Section: Foxc1: a Functional Driver Of Cancer Progression And Metastasismentioning
confidence: 55%
“…Amongst the gastrointestinal cancers, the evidence in support of the prognostic utility of FOXC1 is perhaps most robust in colon cancer. Three independent studies have confirmed the fact that FOXC1 expression status can in fact predict worse overall survival in colon cancer (47)(48)(49). One of these studies reports convincing data with regard to both overall survival and disease-free survival (48).…”
Section: Gastrointestinal Cancersmentioning
confidence: 83%
See 1 more Smart Citation
“…FOXC1 affects gene expression by binding their promoters or cooperating with other factors, and it also participates in signal transduction by working as a substrate of ERK1/2 to be phosphorylated at S272, which could increase its stability by reducing the proteasomal degradation of FOXC1 [75][76][77]. Though Functions of FOXC1 in signal transduction have been well-studied [78][79][80][81], our data suggest that FOXC1 may play unrevealed roles in the epigenetic regulation of gene expression. As seen in Figure 4h, the proteins DNMT1, HDAC2, RBBP4, Yy1, EP300, Trim28, and Smarca1/4/5 are involved in chromatin modification, regulation of chromosomal remodeling and gene expression.…”
Section: Discussionmentioning
confidence: 79%
“…The data accumulated over the years demonstrate the unique behavior of FOXC1 in cancer, particularly in basal-like breast cancer (BLBC) (Wang et al, 2018a). Other studies determined that FOXC1 is significantly involved in breast cancer (BRCA) (Sabapathi et al, 2019) and also colon adenocarcinoma (COAD) (Zhang et al, 2020), pancreatic adenocarcinoma (PAAD) (Subramani et al, 2018), and non-small-cell lung cancer (NSCLC) (Chen et al, 2016). Using genetic epistasis analysis, Liu found that FOXC1 attaches to integrin α7 (ITGA7) and FGFR4 and then activates their expression in metastatic colorectal cancer (CRC).…”
Section: Other Regulatory Factors Of Fgfr4mentioning
confidence: 99%